The Mediating Effect of Inflations on the Effect of Trade Liberalizations and Government Spending Towards Welfare - INDRASWATI, Tri Abdi Reviane (Journal of Advanced Research in Law and Economics, 2017)
The purpose of this study is to find the effect of trade liberalization and government spending on welfare, both directly and indirectly, through the mediation of the inflation rate. The research method used in this research is the Library Research, as a form of research that utilizes the available literature in the form of books, journals, data and other empirical studies. All of the data used in this study are the annual data for each research variable from 1986 to 2015.Based on the results of analysis show that there is significant influence between the variables Liberalism trade and government spending to the inflation rate. But, unlike the effect of government spending on welfare who has no direct influence. However, it was found that the rate of inflation mediating variables influence trade liberalism and government spending on welfare